Roxadustat for anemia in patients with end-stage renal disease incident to dialysis. Issue 9 (25th February 2021) - Provenzano, Robert; Shutov, Evgeny; Eremeeva, Liubov; Korneyeva, Svitlana; Poole, Lona; Saha, Gopal; Bradley, Charles; Eyassu, Meraf; Besarab, Anatole; Leong, Robert; Liu, Cameron S; Neff, Thomas B; et al.
Abstract: Background: We evaluated the efficacy and safety of roxadustat versus epoetin alfa for the treatment of chronic kidney disease-related anemia in patients new to dialysis. Methods: HIMALAYAS was a Phase 3, open-label, epoetin alfa-controlled trial. Eligible adults were incident to hemodialysis/peritoneal dialysis for 2 weeks to ≤4 months prior to randomization and had mean hemoglobin (Hb) ≤10.0 g/dL. Primary endpoints were mean Hb (g/dL) change from baseline averaged over Weeks 28–52 regardless of rescue therapy [non-inferiority criterion: lower limit of 95% confidence interval (CI) for treatment difference >−0.75] and percentage of patients achieving an Hb response between Weeks 1 and 24 censored for rescue therapy (non-inferiority margin for between-group difference −15%). Adverse events were monitored. Results: The intent-to-treat population included patients randomized to roxadustat ( n = 522) or epoetin alfa ( n = 521). Mean (standard deviation) Hb changes from baseline averaged over Weeks 28–52 were 2.57 (1.27) and 2.36 (1.21) in the roxadustat and epoetin alfa groups. Roxadustat was non-inferior [least squares mean difference: 0.18 (95% CI 0.08, 0.29)] to epoetin alfa. Percentages of patients with an Hb response were 88.2% and 84.4% in the roxadustat and epoetin alfa groups, respectively. Roxadustat was non-inferior to epoetin alfa [treatment-group difference 3.5% (95% CI −0.7%, 7.7%)]. Adverse event rates were comparable between treatment groups. Conclusions: Roxadustat was efficacious for correcting and maintaining Hb levels compared with epoetin alfa. Roxadustat had an acceptable safety profile. Graphical Abstract: